Influence of fruit maturity and calyx drying on cape gooseberry (Physalis peruviana l.), stored at 18°C Influencia de la madurez del fruto y del secado del cáliz en uchuva (Physalis peruviana l.), almacenada a 18°C - Moreno Paola; Miranda Diego; Fischer Gerhard; Ávila Jhonn (Acta Agronómica)
Cape gooseberry fruits at the maturity stages 3 (yellow greenish) or 5 (yellow orange) and with calyx drying for 6 hours at 18 or 24ºC, were stored at the temperature of 18ºC and 85 % relative humidity for 20 days, to evaluate physical-chemical and physiological changes. The cape gooseberry, a climacteric fruit, presented the maximum of respiration between 6 and 8 days of storage. The 6th day of storage seems to be crucial due to the very high metabolism and the maximum contents of sugars and acids on this day. Soluble solids tended to increase and the titratable acids went to diminish. The fruit's sugar content was characterized by a major concentration of sucrose, followed by glucose and fructose. While the citric acid showed its highest level at the sixth storage day that of the tartaric acid increased constantly up to 18 days. The fruit maturity stage 3 is that which best conserved the sugars and organic acids evaluated. The maturity index influenced more than calyx drying the postharvest behavior of cape gooseberry. Calyx drying at 24ºC caused the highest climacteric peak and originated the highest loss of fresh weight in fruits harvested at maturity index 5. Key words: Physalis peruviana; respiration; climacteric fruit; Brix degrees; organic acids; sugars. Frutos de uchuva en estados de madurez 3 (amarillo verdoso) ó 5 (amarillo naranja) y con secado del cáliz durante seis horas a 18 y 24ºC, se almacenaron a temperatura ambiente (18ºC) y humedad relativa del 75% durante 20 días, con el fin de evaluar cambios físico-químicos y fisiológicos. La uchuva, fruto climatérico, presentó el máximo de respiración entre los 6 y 8 días de almacenamiento. El día 6 de almacenamiento parece ser crucial debido al metabolismo muy elevado y los contenidos más altos de azúcares y ácidos. Los sólidos solubles totales tendieron a aumentar, la acidez titulable a disminuir. El contenido de azúcares se caracterizó por mayor concentración de sacarosa, seguido por glucosa y fructosa. Mientras el ácido cítrico mostró el nivel más alto a los 6 días de almacenamiento, el del ácido tartárico aumentó constantemente hasta los 18 días. El estado de madurez 3 del fruto conservó mejor los azúcares y ácidos orgánicos. El índice de madurez influyó más que el secado del cáliz, sobre el comportamiento poscosecha de la uchuva. El secado del cáliz a 24ºC causó el pico climatérico más alto, originó la mayor pérdida de peso fresco en frutos cosechados al índice de madurez 5. Palabras claves: Physalis peruviana; respiración; fruto climatérico; grados Brix; ácidos orgánicos; azúcares.